General Bank's Profitability Analysis on The Impact of Going Public Process - Karina Buditianingsih; I Ketut Gunarta (Institut Teknologi Sepuluh Nopember, 2020)
Various reasons underlying the company's owner to Go Public processes such as increasing the company's capital, diversifying shares, overcoming lending constraints. Whatever the underlying reasons, Go Public decisions always have an impact on the company's finances and operations. There is a possibility for companies to not be able to manage funds from the Go Public process, causing a surplus of equity and an impact on decreasing company performance. This research was conducted to determine the impact of Going Public on company performance in terms of profitability. This study uses a purposive sampling technique to produce 3 sample banks that conduct an IPO in the period 2009- 2012 with the BOOK Bank category 2. Post-Go Public company performance is analyzed in terms of profitability using the financial ratios of Net Profit Margin ( NPM) and Gross Profit Margin (GPM). Hypothesis testing in the form of a paired t test was conducted on Net Profit Margin (NPM) and Gross Profit Margin (GPM) for the period of 4 years before and after going Public. The results of this study are expected to find out whether the process of Going Public has an impact on company profitability. In addition, the company's ability to perform cost efficiency can be measured through the use of the ratio of Net Profit Margin (NPM) and Gross Profit Margin (GPM).